2021
DOI: 10.1051/e3sconf/202126401019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the roller pressing of fibrous materials

Abstract: The work is devoted to modeling the regularities of hydraulic pressure distribution and fluid removal from the fibrous material in the contact zone. It was found that the hydraulic pressure in the compression zone increases from zero at the initial point of contact to a maximum at the point of maximum compression of the fibrous material. The patterns of distribution of hydraulic pressure in the recovery zone depend on the length of the section, where the fluid moves from the layer of material to the elastic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…An analysis of the calculated data and curves of hydraulic pressure distribution described by models (11) and (12) showed that they fully correspond to the theoretical conclusions and experimental diagrams of hydraulic pressure given in [5,13,23]. As is known [4,5], the amount of removed fluid flowing along the roll contact curve can be determined by the following expression:…”
supporting
confidence: 65%
“…An analysis of the calculated data and curves of hydraulic pressure distribution described by models (11) and (12) showed that they fully correspond to the theoretical conclusions and experimental diagrams of hydraulic pressure given in [5,13,23]. As is known [4,5], the amount of removed fluid flowing along the roll contact curve can be determined by the following expression:…”
supporting
confidence: 65%
“…Solutions to the problems of contact interaction in roller machines, where the work rolls have an elastic coating, depend on how fully it represents the laws of deformation of the contacting bodies [4,5]. An analysis of the experimental data [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] has shown that, in general, the deformation of such contacting bodies of roller machines is described either by empirical formulas of the form n A   , or by rheological models of the form…”
Section: Introductionmentioning
confidence: 99%
“…Among these processes, the process of pressing the semi-finished leather product after tanning is of particular importance, since this process creates the moisture necessary for subsequent technological processes. Despite numerous studies of the problem of contact interaction and moisture filtration during squeezing, mathematical modeling of the distribution of hydraulic pressures in the process of squeezing the skin is poorly understood [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The fact that the filtering properties of the semi-finished leather product after tanning are not used in solving hydraulic problems indicates that the hydraulic problems in the roller pressing of the skin are poorly understood.…”
Section: Introductionmentioning
confidence: 99%